Taxation and Endogenous Growth in Open Economies - Roubini, Nouriel (IMF Working Papers; Working Paper ;, 1994)
This paper examines the effects of taxation of human capital, physical capital and foreign assets in a multi-sector model of endogenous growth. It is shown that in general the growth rate is reduced by taxes on capital and labor (human capital) income. When the government faces no borrowing constraints and is able to commit to a given set of present and future taxes, it is shown that the optimal tax plan involves high taxation of both capital and labor in the short run. This allows the government to accumulate sufficient assets to finance spending without any recourse to distortionary taxation in the long run. When restrictions to government borrowing and lending are imposed, the model implies that human and physical capital should be taxed similarly.